2020
DOI: 10.3390/ijms21030800
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ1 Regulates Human RANKL-Induced Osteoclastogenesis via Suppression of NFATc1 Expression

Abstract: Osteoclasts are multinucleated giant cells responsible for bone resorption. Various mediators involved in osteoclast differentiation have been investigated as possible therapeutic targets for osteoporosis and rheumatoid arthritis (RA). Although transforming growth factor beta1 (TGFβ1) has been described as one such multifunctional cytokine essential for bone remodeling, its effect on osteoclastogenesis remains controversial. Therefore, we sought to examine the effect of TGFβ1 on osteoclast generation induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 66 publications
(109 reference statements)
0
22
0
Order By: Relevance
“…21,22 However, a recent report showed that TGF-β1 suppresses human RANKL-induced human osteoclast development and bone resorption and identified a potential therapeutic target for RA. 23 We believe that the opposing effects of TGF-β1 may be due to difference in the experimental cells used in previous studies. 23 Macrophages are the major source of IL-1β and contribute to tissue destruction and pain in RA patients.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…21,22 However, a recent report showed that TGF-β1 suppresses human RANKL-induced human osteoclast development and bone resorption and identified a potential therapeutic target for RA. 23 We believe that the opposing effects of TGF-β1 may be due to difference in the experimental cells used in previous studies. 23 Macrophages are the major source of IL-1β and contribute to tissue destruction and pain in RA patients.…”
Section: Discussionmentioning
confidence: 98%
“…23 We believe that the opposing effects of TGF-β1 may be due to difference in the experimental cells used in previous studies. 23 Macrophages are the major source of IL-1β and contribute to tissue destruction and pain in RA patients. In this study, LPS and ATP treatment contributed to the inflammatory environment in THP-1-derived macrophages, and IL-1β and caspase-1 levels were higher following the inhibition of FURIN expression.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nuclear factor of activated T cells cytoplasmic 1 (NFATc1) is a master regulator of osteoclast differentiation (Okamoto and Takayanagi, 2011 ). Some studies have shown that TGF-β1 directly down-regulates NFATc1 activity by blocking the p65 in the receptor activator and then inhibits the generation and bone resorption of osteoclasts ( Figure 2 ) (Tokunaga et al, 2020 ). Recently, the role of the NEMO protein (a core component of the NF-kB signaling pathway) in mouse bone marrow macrophages was investigated that if the lysine-270 (NEMO-Lys270) in NEMO protein was mutated to Ala, the NF-kB signal in bone marrow macrophages would lose control, leading to the accelerated production of osteoclasts (Adapala et al, 2020 ).…”
Section: Communications Between Macrophages and Bone Cellsmentioning
confidence: 99%
“…The RANKL-induced osteoclast activation was mediated by MAPK signaling [25][26][27][28]. Thus, we evaluated whether MAPK signaling has a role in IL-16-mediated osteoclast activation.…”
Section: Effect Of Il-16 On Osteoclast Activation Through P38 and Jnkmentioning
confidence: 99%